Conservation, Surface Exposure, and In Vivo Expression of the Frp Family of Iron-Regulated Cell Wall Proteins in Staphylococcus aureus - Morrissey, Julie A. (American Society for Microbiology, 2002)
Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis identified two conserved, immunogenic Staphylococcus aureus cell wall proteins, of 40 and 87 kDa, expressed under iron-restricted growth conditions in vitro and in vivo. N-terminal sequencing and subsequent genome analysis showed that these proteins are encoded by adjacent monocistronic open reading frames designated frpA and frpB, respectively. Studies with an S. aureus fur mutant confirmed that expression of FrpA and FrpB is regulated by Fur but that there also appears to be differential expression of these proteins in different iron-restricted media in vitro. FrpA and FrpB share some amino acid sequence homology with each other and with a putative S. aureus membrane protein, FrpC. frpC is the first gene of a Fur-regulated operon encoding four proteins of unknown function (FrpC, -D, -G, and -H) and the binding protein (FrpE) and permease (FrpF) of a putative iron transporter. Antisense mutagenesis and bioassays showed that FrpA and FrpB are not required for growth of S. aureus under iron-restricted conditions in vitro and do not appear to be involved in the transport of iron from siderophores or in binding of hemin. Further phenotypic analysis suggested that FrpA may be involved in adhesion of S. aureus to plastic in vitro. Binding of S. aureus to microtiter wells was found to be iron regulated, and iron-restricted S. aureus containing antisense frpA or frpAB but not frpB constructs showed reduced binding compared to vector construct controls.